Morphological variation in Acrossocheilus hemispinus (Teleostei: Cyprinidae: Barbinae), with comments on its taxonomic status - Yuan, Le-Yang; Zhang, E (Zootaxa, 2010)
Differences in coloration and morphology between two subspecies of Acrossocheilus hemispinus were investigated based on museum-stored and freshly-caught specimens. There are marked differences in the coloration of either juveniles or adults, and in sexual dimorphism, between A. h. hemispinus and A. h. cinctus. Multivariate analysis of morphometric data too, shows the two taxa to be distinguishable from each other. Differences in body coloration and morphometric characters coincide with those of the mouthpart structure and the coiling pattern of the intestine in A. h. hemispinus and A. h. cinctus. Morphological distinction, coupled with different habitat and food preferences, supports the taxonomic elevation of the two hitherto subspecific populations of A. hemispinus to species.